Efektivitas Augmented Reality Dalam Meningkatkan Akurasi Gerak Pada Pembelajaran Tari Tradisional - Nurmalena; Citrawati, AAIA; Oktavianus; Hardi (Information Technology Education Department, 2026)
This study aims to analyze the effectiveness of Augmented Reality (AR) in improving motion accuracy in dance movement learning compared to conventional methods. The study used a quasi-experimental design, with an experimental group using AR media and a control group using conventional learning. Data were collected through pretest and posttest motion accuracy measurements, then analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, and ANCOVA with the pretest as a covariate. Furthermore, instrument reliability was tested using the Intraclass Correlation Coefficient (ICC). The results showed that both groups experienced significant improvement, but the AR group showed a higher improvement than the control group. Further testing revealed significant differences between the two groups in both the posttest and gain scores, with large to very large effect sizes. The ANCOVA analysis also indicated that the effect of AR remained significant after controlling for students' initial abilities. The ICC value of 0.88 indicates that the measurement instrument has good reliability. These findings suggest that Augmented Reality has strong potential for improving motor skills through the presentation of interactive three-dimensional visualizations, which support the process of observing, understanding, and reproducing movement more effectively. However, these results need to be interpreted with caution considering the limitations of the non-randomized study design. Further research is recommended to examine the long-term effectiveness and moderating factors influencing the success of AR-based learning.